Modelling Stochastic Foam Geometries for FE Simulations Using 3D Voronoi Cells - Siegkas, Petros (My University, 2014)
A method for generating realistic foam geometries is developed for modelling the structure of stochastic foams. The method employs 3D Voronoi cells as pores. The virtual geometries are subjected to loading with the use of finite element methods and the results are compared to experimental data for open cell Titanium foams. The method applies statistical control to geometrical characteristics and it's used to either replicate or virtually generate prototype foam structures.
Keywords: Voronoi Simulation; Finite Element; Microscale; Modelling; Titanium Foam